KAJIAN SOSIOLOGI TENTANG TINGKAT KESADARAN PENDIDIKAN PADA MASYARAKAT DESA LABUAN KAPELAK KECAMATAN BANGGAI SELATAN KABUPATEN BANGGAI LAUT - Ladaria, Yessi H.; Juliana Lumintang, Juliana Lumintang; Paat, Cornelius J. (HOLISTIK, Journal Of Social and Culture, 2020)
Education is fundamental in human life. Education can be an indicator of the level of social life in society. Education awareness affects one's education level, the higher the education the higher the social status obtained in society.This study aims to determine the study of sociology about the level of education awareness in the labuan village of KapuanKapelak, the district of southiproudi district of the sea proud of the importance of education awareness. This research uses descriptive qualitative research methods, data sources obtained from primary data and secondary data from research study locations. Data collection techniques using observation, interviews and documentation.The results of the study concluded that most of the community were still less aware of the importance of education for survival. The government's suggestion to increase efforts to develop public awareness of the importance of education in the form of counseling and assistance to reduce school costs, especially for the poor.Keywords: Level of awareness, Education, Society